Trace element contents in marls of the Ptolemais - Amynteon lignite basin, Western Macedonia, Greece - ΣΑΧΑΝΙΔΗΣ, Χ.; ΓΕΩΡΓΑΚΟΠΟΥΛΟΣ, Α.; ΦΙΛΙΠΠΙΔΗΣ, Α.; ΚΑΣΩΛΗ-ΦΟΥΡΝΑΡΑΚΗ, Α. (Bulletin of the Geological Society of Greece, 2001)
Sixty-five marl samples were collected from the outcrops of six active and one abandoned mine of Ptolemais-Amynteon Lignite Center, Northern Greece. Core samples were also collected from the West Field, a Neogene lignite deposit located at the same area. The concentrations of 39 trace elements were determined using Instrumental Neutron Activation analysis (INAA) and Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Carbon and sulfur contents and the loss on ignition of the samples were also determined. The classification of the trace elements concentrations in each mine and their statistical processing allows determining the horizontal and vertical distribution in the coal deposits and in the entire basin. Regarding the vertical distribution of elements and geochemical groups, significant variations of the concentrations in both the different marl seams and the upper, intermediate and lower lignite seams were determined. The mining, processing, transportation, storage and utilization of marls release, among others, some amounts of trace elements into the environment. However, the low concentrations of all trace elements, except Pb in the South field, compared to the upper mean values of world rocks Crust (W.C-U.M.V) (enrichement factor <0.8) is of great environmental concern and prove the non hazardous role of the marl during mining, beneficiation and usage.